2021
DOI: 10.1186/s41182-021-00362-8
|View full text |Cite
|
Sign up to set email alerts
|

Urogenital schistosomiasis burden in school-aged children in Tiko, Cameroon: a cross-sectional study on prevalence, intensity, knowledge and risk factors

Abstract: Background This study aimed at determining urogenital schistosomiasis (UGS) prevalence, intensity, knowledge and risk factors in school-aged children (SAC) in the new endemic focus of Tiko, Cameroon. Methods A cross-sectional study including 389 SAC of both sexes aged 5–15 years was carried out between April and June 2018. A structured questionnaire was used to collect demographic data, clinical and predisposing factors. Urine sample collected was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
3
11
1
Order By: Relevance
“…Additionally, this part of the country is regularly targeted by the National Program for the Fight against Schistosomiasis and Intestinal Helminthiasis (NPFSIH). In comparison with previous studies conducted on the national territory, this prevalence is higher than those observed by Dankoni et al [14] in the district of Kékem, West-Cameroon, Dankoni et al [10] in the district of Taïbong-Dziguilao, northern region and Sumbele et al [11] in Tiko in the South West region who observed 1.7%, 5.83% and 37.0% respectively. However, this prevalence is similar to those observed by Njunda et al [12], a study conducted among primary school children in the locality of Magba, West-Cameroon, which observed a prevalence of 41.1% and Ntonifor et al [15] in Munyenge in the South-west of the country who found a prevalence of 40.27%.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Additionally, this part of the country is regularly targeted by the National Program for the Fight against Schistosomiasis and Intestinal Helminthiasis (NPFSIH). In comparison with previous studies conducted on the national territory, this prevalence is higher than those observed by Dankoni et al [14] in the district of Kékem, West-Cameroon, Dankoni et al [10] in the district of Taïbong-Dziguilao, northern region and Sumbele et al [11] in Tiko in the South West region who observed 1.7%, 5.83% and 37.0% respectively. However, this prevalence is similar to those observed by Njunda et al [12], a study conducted among primary school children in the locality of Magba, West-Cameroon, which observed a prevalence of 41.1% and Ntonifor et al [15] in Munyenge in the South-west of the country who found a prevalence of 40.27%.…”
Section: Discussioncontrasting
confidence: 66%
“…Thus, the study conducted in the district of Taïbong-Dziguilao in the northern region found a S. haematobium infestation of 5.83% [10]. This prevalence is relatively low compared to those observed by Sumbele et al [11] and Njunda et al [12] who observed a prevalence of 37.0% and 41.1% respectively among school children in the South West and Magba sub-division in the West region. In view of the high prevalence of US and the different variations observed on the national territory, it is necessary to carry out new investigations on this morbid and fatal parasitosis in primary school pupils.…”
Section: Introductionmentioning
confidence: 68%
“…The prevalence of urogenital schistosomiasis was also significantly higher among women who swam in river water, while none of the women who did not swim in river water had urogenital schistosomiasis. This indicates that people are at risk of infection when they use unsafe water [ 13 , 17 ]. Thus, in addition to mass chemotherapy, clean water supply and behavioral change interventions, such as avoiding domestic and recreational activities including swimming or fishing in infested water, can help to interrupt the transmission of schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, temperature and altitude in uence the survival and reproduction of the intermediate host snail, and rainfall contributes to the creation of temporary snail habitats [9]. Sociodemographic factors such as age [6, 10,11] and gender [10,12] may also affect the prevalence of infection. School-aged children and young adults, for instance, are at a higher risk of infection due to their frequent water contact activities [13].…”
Section: Epidemiological Status In Nigeriamentioning
confidence: 99%